KNOWLEDGE OF ADOLESCENT GIRLS ABOUT THE RISKS OF TEEN PREGNANCY IN CLASS VIII SMP NEGERI 3 PRACIMANTORO WONOGIRI - Ristyani Eki Pratiwi; Suroso .; Dwi Retna P (STIKES DUTAGAMA KLATEN, 2013)
Background: Knowledge of adolescent reproductive health is needed, so they can avoid an unwanted pregnancy, protected from sexually transmitted infections, Early marriage, expelled from school, unsafe abortion, and can grow into sexually healthy adults.Teen pregnancy rate in the 15-19 age Indonesia is still very high. From 2006 to 2010 an increase in teenage pregnancy rate of 15.6% (BKKBN, 2006). Research Purpose: To determine the knowledge of adolescent girls about the risks of teen pregnancy in class VIII SMP Negeri 3 Pracimantoro WonogiriMethods: This study used a descriptive quantitative research methods. Total population is 44 students with using sampling a total sampling, thus taking the total number of population of 44 students as the sample.Data retrieval techniques with enclosed questionnaire. Analysis of the data in this study using frequency distribution, the data presented in the form of narrative and tables. The research was conducted on May 27, 2013. Results: Knowledge of adolescent girls about the risks of teen pregnancy in SMP Negeri 3 Pracimantoro Wonogiri in good category there are 38 respondents (86.36%), there are enough categories 6 respondents (13.64%), no less category.The Conclusion: Knowledge of adolescent girls about the risks of teen pregnancy in SMP Negeri 3 Pracimantoro Wonogiri most are in good category (86.36%).